Systematic Literature Review: TPACK-Integrated Design Thinking in Education (Lembaga Pengembangan Kinerja Dosen, 2023)
This research aims to analyze design thinking integrated with technological pedagogical content knowledge (TPACK) in ducation. This research is a type of systematic literature review (SLR) research with the PRISMA method. The data sources in the study came from 10 national and international journals published between 2018- 2023 and indexed by SINTA, Scopus, and WOS. The search for data sources comes from Google Scholar, MPDI, ScienceDirect, Wiley, and Eric. The analysis shows that 1) TPACK-integrated design thinking has a positive impact on the learning process, and 2) design thinking integrated with TPACK in education has a variety of forms both in theory and practice. Based on these findings, it can be concluded that the concept of design thinking integrated with TPACK is very necessary to be developed in the education system in Indonesia. Design thinking integrated with TPACK is able to encourage students' critical thinking skills and creativity in learning.